(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
In history, quantitative development data can be used as important data in building a historiography. This article aims to reconstruct the history of general education development by utilizing quantitative data in Pekalongan City during the Pelita V era (1989-1994). Pekalongan City itself is an important city that was once the capital of the Pekalongan Residency which was projected as a trading city where the educational aspect was important to build. This article was written using the historical method with stages of heuristics, criticism, interpretation, and historiography. The main data source is statistical data obtained from Pekalongan report data in figures issued by BPS, as well as government policy archives stored at the City Government Archives Office. The data obtained was then analyzed using a development history approach from a development politics perspective. Based on the results of the analysis, it was found that the condition of general education at the primary and secondary levels in Pekalongan City in Pelita V, seen from the aspect of the number of schools, teachers and students, generally experienced fluctuations/dynamics. In this case, the development of general education at the primary level at PELITA V in Pekalongan City is going well, even though there is inequality. At the secondary level, both junior and senior educational development tends to be stagnant